An industrial quality control study on Cathay Pacific Steel Corporation - Aquino, Diana Sylvia Z.; Cruz, Jennifer; Solano, Nina Patricia (Diliman, Quezon City College of Engineering, 2004)
Cathay Pacific Steel Corporation is the leading manufacture of reinforcing steel bars in the country. This study includes the quality operations and systems of the company. Its main objective is to employ the newly acquired knowledge in the course regarding statistical quality control to make improvements in the quality systems of the company. The study on Cathay Pacific Steel Corporation would be focusing on the quality operations and systems of the company. This includes an in-depth analysis of their quality process methods, inspection and results. The group's study is restricted to only three sizes of the company's reinforcing bars : 10 mm, 12 mm and 16 mm. These types of steel bars have the highest demand from the consumers, thus generating a higher need to undergo more thorough inspection tests. With the aid of different quality control techniques such as Statistical Process Control, Process Capability Analysis and Failure Mode and Effect Analysis and some knowledge learned in Methods Engineering such as construction of cause and effect diagram and pareto charts, analysis of the company's quality process methods involving the top three mostly manufactured steel bars was conducted. Study showed that there already exists a sound quality system in the company, however minor problems which can further be improved still exist and this is where the group focused. The group established that occurrence of failure of rebars is caused by the top three noncompliance with specifications, namely Tensile Strength, Yield Strength and Actual Height Tolerance of Lugs. The noncompliance of these specifications was due to problems regarding the workers, methods, machines and raw materials used. The group also found out that the company does not currently conduct Statistical Process Control and must employ this to improve their quality systems. Control Charts for the mean and range of the steel bars were used to analyze the variations in the products. Based on the results of the Process Capability Analysis and Shewhart Tests, the processes of CAPASCO with regards to the yield of strength, tensile strength, and actual height tolerance are mostly in-control although some out of control data points may be observed in the charts. The quality systems of CAPASCO proved to conform to the standards specified by the industry (the Philippine National Standards by the Department of Trade and Industry). Recommendations and implementations were based on the minor problems identified in the paper. The general recommendations made besides the implementation of Statistical Process Control were proper maintenance of machines, training for operators and application of rectifying inspection. The group also formulated a recommendation for a new sampling plan and sample size, a recommendation for standardized visual attributes inspection and sampling plan, and lastly, a recommendation for a new acceptance sampling plan for variables. Improvements in CAPASCO, if the group's recommendation is implemented, can be perceived through the increase in productivity and minimized variation in the steel bars.
Feasibility study
Keywords: Cathay Pacific Steel Corporation; Steel industry and trade; Quality control